Impact of the COVID-19 pandemic on hepatitis C virus screening in provincial prisons in Montreal, Quebec, Canada - Kronfli, Nadine; Leone, Frederic; Dussault, Camille; Miliani, Giovanni; Gallant, Elvira; Potter, Molly; Cox, Joseph (Frontiers in Public Health, 2024)
Background Little is known about the impact of the COVID-19 pandemic on hepatitis C (HCV) screening efforts in carceral settings. We explored the impact of the pandemic on HCV screening in two of Quebec’s largest provincial prisons. Methods Retrospective data of HCV-related laboratory tests between July 2018 and February 2022 at l’Établissement de détention de Montréal (EDM) and l’Établissement de détention de Rivière-des-Prairies (EDRDP) were obtained. To examine the association between the pandemic and the number of HCV-antibody (HCV-Ab) tests, a three-level time period variable was created: pre-outbreak, outbreak, and post-outbreak. Negative binomial regression (with monthly admissions as an offset) was used to assess the change in HCV-Ab tests across time periods and by prisons. Adjusted odds ratios (aOR) with 95% confidence intervals (95% CI) were calculated. Results A total of 1,790 HCV-Ab tests were performed; 56 (3%) were positive. Among these, 44 (79%) HCV RNA tests were performed; 23 (52%) were positive. There was a significant decrease in HCV-Ab screening at EDM during the outbreak (aOR 0.29; 95% CI 0.17–0.48) and post-outbreak (aOR 0.49; 95% CI 0.35–0.69) periods, compared to the pre-outbreak period. There was no significant change in HCV-Ab screening at EDRDP during the outbreak (aOR 0.98; 95% CI 0.49–2.11) but a significant increase in HCV-Ab screening post-outbreak (aOR 1.66; 95% CI 1.04–2.72). Conclusion The COVID-19 pandemic negatively affected HCV screening at EDM but had minimal impact at EDRDP. To eliminate HCV from carceral settings, minimizing screening interruptions during future outbreaks and combined HCV/SARS-CoV-2 screening should be prioritized.